PERAWATAN ENDODONTIK KONVENSIONAL PADA GIGI INSISIF LATERAL ATAS DENGAN KISTA RADIKULAR (LAPORAN KASUS) - Buddiwati Punta; Winiarti Sidharta (Faculty of Dentistry, Universitas Indonesia, 2015)
It has been shown that more than 40 percent of the apical radiolucencies are radicular cyst, numerous endodontist claims that from 85 to 90 percent of apical lesions disappear or become reduced in size following conservative endodontic treatment and do not require surgical intervention. Maxillary teeth are more frequently susceptible to trauma and there are numerous morphologic anomalies associated with maxillary incisors especially lateral incisors its call palato-radicular groove (PRG), its caused non vital have been implicated in formation of periapical lesions. Periapical lesions can be cured by conventional endodontic treatment used Ca(OH)2 as an intracanal medication. One case with radicular cyst on the maxillary lateral incisors because of trauma 2 years ago will be presented. Fiffteenth months during treatment showed that the cyst reduced in size and symptomless.